SISTEM INFORMASI MANAJEMAN PROMOSI DAN LAYANAN PONDOK PESANTREN - Wahyuningsih, Sulis; Putra, Riyan Rinanda Gilang; Zumaroh, Lilik (STMIK Pringsewu, 2024)
The internet is an example of how fast and increasingly sophisticated information technology advances. Many services and information are available on the internet. Many services and information are available on the internet. People can obtain information more quickly and accurately thanks to the Internet. In terms of application, information technology can be put to its best use in the field of education, namely on websites hosted on the Internet and functioning as publishing and school registration platforms to improve teaching standards. Especially in terms of socialization in the field of education, such as the manual for the process of accepting new students at the Ummul Quro' Islamic Boarding School. Therefore, to disseminate information about the Ummul Quro Islamic Boarding School and other related topics, there must be an information system. Waterfall is a method used by software developers and software creators. The waterfall method is used because the process takes place sequentially and systematically starting from the planning stage to the management stage. This research resulted in the application of an information system as a medium for delivering information that is easily accessible and produces good service processes in Islamic boarding schools such as registering new students. By implementing an information system to input various information and data about Islamic boarding schools, managers can enter data more efficiently, and A part from that, using a website can expedite the data recording process, reduce data entry errors, and expedite registration procedures.